Successional Change of the Fungal Microbiome Pine Seedling Roots Inoculated With Tricholoma matsutake - Park, Ki Hyeong; Oh, Seung-Yoon; Yoo, Shinnam; Park, Myung Soo; Fong, Jonathan J.; Lim, Young Woon (Frontiers in Microbiology, 2020)
Pine mushroom (Tricholoma matsutake) is an ectomycorrhizal fungus that produces a commercially-valuable and edible mushrooms. Attempts on the artificial cultivation of T. matsutake has far been unsuccessful. One method to induce the production of the fruiting bodies of T. matsutake in the wild is shiro transplantation. In vitro ectomycorrhization of T. matsutake with seedlings of Pinus densiflora was reliably successful, but field trials showed limited production of the fruiting bodies. Few studies have been done to test whether T. matsutake persists on pine seedling roots in the wild or gets replaced by other fungi. Here, we investigated the composition and the interaction of the root fungal microbiome of P. densiflora seedlings inoculated with T. matsutake, over 3 years after field transplantation using high-throughput sequencing. We found a decline of T. matsutake colonization on pine roots and succession of mycorrhizal fungi as P. densiflora seedlings grew. Early root microbiome was colonized by fast-growing saprotrophic Ascomycota, then was replaced by early stage ectomycorrhiza such as Wilcoxina. At the end, more competitive Suillus species dominated the host roots. Most of the major OTUs had negative or neutral correlation with T. matsutake, but several saprotrophic/plant pathogenic species in genera Fusarium, Oidiodendron, and Trichoderma had positive correlation with T. matsutake. Four keystone species (Suillus granulatus, Dactylonectria anthuriicola, Fusarium oxysporum, and F. trincintum) were identified during succession, of which had a positive (F. oxysporum, and F. trincintum) or a negative correlation (S. granulatus, D. anthuriicola) with T. matsutake. These findings have important implications for further studies on the artificial cultivation of T. matsutake.